Analysis of Sabit Kick Agility in Pencak Silat Sports - Wijaya, Muhammad Riski Adi; Hariono, Awan; Syaifullah, Rony; Nugroho, Haris (PROSIDING SEMINAR KESEHATAN MASYARAKAT, 2024)
Background: In the realm of Pencak Silat, the speed of the sabit kick is a critical aspect that distinguishes between an athlete's skill and proficiency. A technical movement must possess an optimal level of effectiveness and efficiency. Pencak Silat is a traditional Indonesian martial art that encompasses a variety of techniques and movements, one of which is the sabit kick. The sabit kick is a crucial technique in Pencak Silat, requiring agility, precision, and strength to be executed effectively. In Pencak Silat competitions, the sabit kick is frequently used to score points or even to defeat an opponent. Therefore, analyzing the agility involved in executing the sabit kick in a competitive context is essential. An athlete’s ability to perform the sabit kick quickly and accurately can be a decisive factor in the outcome of a match. Good agility enables athletes to respond swiftly to their opponent’s movements and to execute techniques at the right moment. Method: This study employs a quantitative descriptive approach. The research subjects consisted of 61 members of Tapak Suci MTS Muhammadiyah Pekalongan City, selected using a total sampling technique. Data collection was carried out through tests and measurements of sabit kick agility. The test procedure involved subjects performing sabit kicks with both the right and left legs, maneuvering over 30 cm high cones within 15 seconds. Subsequently, data analysis was conducted using percentage techniques to understand the frequency distribution of the test results. Result: The results of the sabit kick agility test for Tapak Suci MBS KH. Mas Mansyur athletes revealed that 8.19% or 5 athletes were categorized as sufficient, 44.26% or 27 athletes as poor, and 47.54% or 29 athletes as very poor. Conclusion: to achieve optimal performance, enhancing the agility of the sabit kick must be a top priority in the development of training programs at Tapak Suci MBS KH. Mas Mansyur.